Pengembangan Lembar Kerja Siswa Inovatif Berbasis Proyek: Meningkatkan Hasil Belajar - Ilham Nazaruddin; Puji Rahmawati (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2020)
This study aims to: (1) develop project-based student worksheet media on the concept of respiratory organs in humans; (2) reveal the feasibility of developing student worksheet media according to media experts, material experts and students; and (3) improving student natural science learning outcomes through innovative student-based worksheet media based on project-based learning. This research was employed a development research design that refers to the ADDIE model. The research subject was elementary school fifth-grade students. Data collection techniques were tests and non-tests. The data instruments were expert validation questionnaires, student response questionnaires, and multiple-choice questions. The feasibility of instructional media was developed and analyzed using the conversion of five quantitative categories. The results of this development were project-based learning student worksheet media. Based on validation, response, and questions, the project-based student worksheet media i is feasible according to media experts, material experts, and students. Keywords: learning outcomes, project-based learning, innovative student worksheets